Prurigo Nodularis in a Patient With Primary B‐Cell Immunodeficiency Successfully Treated With Low‐Dose Methotrexate: A Case Report - Hamad El Hajj; Dima Jeha; Jennifer Abi Younis; Peter Noun; Maya Habre (Clinical Case Reports)
ABSTRACT Prurigo nodularis is a chronic pruritic condition that leads to a vicious itch‐scratch cycle, which can significantly impair quality of life. Low‐dose methotrexate is an effective option for patients with chronic nodular prurigo not responding to topical therapy, offering a favorable safety profile and improving their quality of life.